Microgravity and Human Body: Unraveling the Potential Role of Heat-Shock Proteins in Spaceflight and Future Space Missions - Olga Maria Manna; Stefano Burgio; Domiziana Picone; Adelaide Carista; Alessandro Pitruzzella; Alberto Fucarino; Fabio Bucchieri (Biology)
In recent years, the increasing number of long-duration space missions has prompted the scientific community to undertake a more comprehensive examination of the impact of microgravity on the human body during spaceflight. This review aims to assess the current knowledge regarding the consequences of exposure to an extreme environment, like microgravity, on the human body, focusing on the role of heat-shock proteins (HSPs). Previous studies have demonstrated that long-term exposure to microgravity during spaceflight can cause various changes in the human body, such as muscle atrophy, changes in muscle fiber composition, cardiovascular function, bone density, and even immune system functions. It has been postulated that heat-shock proteins (HSPs) may play a role in mitigating the harmful effects of microgravity-induced stress. According to past studies, heat-shock proteins (HSPs) are upregulated under simulated microgravity conditions. This upregulation assists in the maintenance of the proper folding and function of other proteins during stressful conditions, thereby safeguarding the physiological systems of organisms from the detrimental effects of microgravity. HSPs could also be used as biomarkers to assess the level of cellular stress in tissues and cells exposed to microgravity. Therefore, modulation of HSPs by drugs and genetic or environmental techniques could prove to be a potential therapeutic strategy to reduce the negative physiological consequences of long-duration spaceflight in astronauts.